Assessment of injuries in small scale sawmill industry of South Western Nigeria (2010)
Body injuries sustained in sawmill industry as a result of miII activities in Ondo, Oyo and Osun states in the Western part of Nigeria was investigated. Nigeria Sawmill Industries are essentially distributed between small, medium and large scale in the proportion of 81%: 13%: 6% respectively (RMROC, 2003). A survey involving the use of questionnaire, participatory approaches, on-the-spot assessments and interviews were used as tools for investigation. A total of 140 injury cases were recorded among 64 workers from investigated sawmills.The data collected were subjected to descriptive statistics. Results indicated that mill workers suffers highest injury rate of 83% while moving logs to mill from log yard or stack while timber stacking accident is the least at 36%. Other accident cases recorded include; log transport to the mill is 22%, milling operation 41% and maintenance accident 38%. Injuries occurring to body area include upper limb injuries (Neck and head, arm, wrist, hand and shoulder) 68%, back and lower back injuries 58%, and less prominent lower limb (Legs, knees and ankle) injuries at 13%.